Magnesium, Oxidative Stress, Inflammation, and Cardiovascular Disease - Man Liu; Samuel C. Dudley (MDPI AG, 2020)
Hypomagnesemia is commonly observed in heart failure, diabetes mellitus, hypertension, and cardiovascular diseases. Low serum magnesium (Mg) is a predictor for cardiovascular and all-cause mortality and treating Mg deficiency may help prevent cardiovascular disease. In this review, we discuss the possible mechanisms by which Mg deficiency plays detrimental roles in cardiovascular diseases and review the results of clinical trials of Mg supplementation for heart failure, arrhythmias and other cardiovascular diseases.